Universal Credit, gender and unpaid childcare: Mothers' accounts of the new welfare conditionality regime. (August 2020) - Andersen, Kate
The introduction of Universal Credit, a new social assistance benefit for working age people in the UK, constitutes radical welfare reform and entails a significant intensification and expansion of welfare conditionality. Numerically, women are disproportionately affected by the conditionality regime for main carers of children within Universal Credit. Under this new benefit, couples have to nominate as 'responsible carer' the person in the household primarily responsible for the care of dependent children. Lone parents are automatically designated as the 'responsible carer'. The responsible carer is subject to varying levels of conditionality (depending on the youngest child's age) and faces benefit sanctions for non-compliance. To investigate the gendered implications of conditionality for responsible carers within Universal Credit, a small-scale qualitative study was carried out. The study's findings show that the conditionality within Universal Credit devalues unpaid childcare and subjects mothers to conflicting responsibilities of mandatory work-related requirements and unpaid childcare.